NEOLIBERALISM AND INEQUALITY IN POSTAPARTHEID SOUTH AFRICA (The Pretoria Student Law Review, 2021)
The article will uncover how socio-economic inequality is prevalent in our democratic dispensation using mainly two theories: Critical Race Theory and Critical Legal Studies. The latter theories provide the lens through which we can evaluate, analyse, and criticise neoliberal policies in our contemporary society. I will argue that it is preposterous to theorise and understand neoliberalism and race as two separate entities that sometimes interconnect.2 The article will outline how race and neoliberalism are co-constitutive.3 In explaining the concept of neoliberalism, the article will also answer pertinent questions arising in South Africa’s contemporary context such as: why do the black- majority remain structurally poor in ‘post-apartheid’ South Africa when it is thought to be the best and most progressive constitution (with first 1st, 2nd, and 3rd general rights) in the world? And who benefits from these policies since socioeconomic inequalities have deepened? Lastly, I will come up with a well-thought alternative that best fits our democratic dispensation.
Keywords: socio-economic inequality; Critical Race Theory; Critical Legal Studies; neoliberal policies